Using body mass index ignores the intensive training of elite special force personnel. Issue 11 (August 2019) - Tafeit, Erwin; Cvirn, Gerhard; Lamprecht, Manfred; Hohensinn, Markus; Moeller, Reinhard; Hamlin, Michael; Horejsi, Renate
Body mass index is a common and well-known measure in daily life. A body mass index higher than 25 is assumed to be an indicator for overweight and obesity and a high amount of total body fat. But body mass index overestimates body fat in subjects with high muscle mass and underestimates it in persons with a low lean body mass, especially in elderly and diseased persons. In the present study, we investigate the performance of the body mass index as a measure of body fatness and its ability to distinguish between well-trained and untrained subjects. Twenty-one well-trained male members of a police task force named "Cobra" and 38 non-active controls, matched by age, weight and height were participants of the study. The age range of these subjects was between 30 and 45 years. Subcutaneous adipose tissue thicknesses and body fat distributions were measured non-invasively by an optical device named the "Lipometer." Statistics were performed with SPSS. We found that the body mass index did not show a difference between the two groups, whereas all Lipometer results were able to discriminate significantly between the trained and untrained subjects. Furthermore, the receiver operating characteristic curve analysis was calculated and all Lipometer measurements provided significant results up to a correct classification of all subjects of 86.4%, which was for the lateral thigh body site. In conclusion, the body mass index was not able to recognize the difference between trained and untrained participants, while body fat distribution measured with the Lipometer was able to distinguish more clearly the large body fat differences between these two groups. Impact statement: Body mass index (BMI) is a common measure of body fatness but overestimates body fat in subjects with high muscle mass. We have developed previously a device named "Lipometer, " an alternative way to measure body fatness. We show herein that the Lipometer is able to distinguish more clearly (than the BMI) the large body fat differences between well-trained and untrained subjects. Thus, the Lipometer is superior to BMI with respect to body fat measurements.